Notes on the feeding behaviour and swimming pattern of Manta alfredi (Chondrichthyes, Mobulidae) in the Red Sea - Fazzano Gadig, Otto Bismarck [UNESP]; Garrone Neto, Domingos [UNESP] (Springer, 2014)
The feeding behaviour and the swimming pattern of the reef manta (Manta alfredi) are described based on video recordings conducted in Sudan, Red Sea, Indian Ocean, during June 2001. Three circular swimming patterns are described: horizontal circle pattern, inclined circle pattern and double circle pattern, related to feedings on zooplankton distributed in the water column. The observation of circle-like swimming patterns for reef manta rays in shallow waters expands our knowledge about M. alfredi and suggests that the distribution and abundance of zooplankton influence the occurrence and group size of this species in the studied area, as reported from other localities for Manta species.
Keywords: Mobulid rays; Elasmobranch behaviour; Distribution; IndianOcean; Sudan